THE EFFECT OF CONVENIENCE, USEFULNESS AND CREDIBILITY ON REPEAT USE INTEREST MEDIATED BY USAGE SATISFACTION ON BANK JATENG LAKU PANDAI - Willi Agung Prabowo; I Made Sukresna (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2025)
In the increasingly developing digital era, customer satisfaction and loyalty to a product or service are the main factors in maintaining business competitiveness. Factors such as perceived ease, perceived usefulness, and perceived credibility play an important role in shaping customer experience, which can ultimately influence their decision to continue using the product or service. This study aims to analyze the effect of perceived ease, perceived usefulness, and perceived credibility on customer satisfaction and the intention to use a product or service repeatedly. In addition, this study also explores the role of customer satisfaction as a mediating variable. This research method uses a quantitative approach with a survey method involving 100 respondents of Laku Pandai Bank Jateng Semarang Region users as research samples. Data analysis techniques were carried out using Structural Equation Modeling (SEM) with the help of PLS ​​4.0 software to test the influence of research variables. The results of the study indicate that Perceived usefulness towards customer satisfaction has a significant effect with a p-value of 0.001. Perceived ease of use towards customer satisfaction has a significant effect with a p-value = 0.013. Perceived credibility towards customer satisfaction has a significant effect with a p-value of 0.005. Perceived usefulness towards repeat usage intention has a significant effect with a p-value of 0.000. Perceived ease of use towards repeat usage intention has a significant effect with a p-value of 0.000. Perceived credibility towards repeat usage intention has a significant effect with a p-value of 0.002. Customer satisfaction is proven to be a mediator that strengthens the relationship between the three independent variables towards repeat usage intention. A significant indirect effect was found in the relationship between perceived usefulness (β = 0.087, p = 0.023), perceived ease of use (β = 0.068, p = 0.041), and perceived credibility (β = 0.074, p = 0.026) towards repeat usage intention through customer satisfaction. The R-square value shows that this model can explain 32.1% of the variability in customer satisfaction and 64.2% of the variability in repeat usage intention, indicating that other factors outside the model can still influence the dependent variables.